Corporate Crime in Illegal Fishing Practices and Its Enforcement in Indonesia - Imas solehayati; Sahat Maruli Tua Situmeang (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Indonesia is one of the largest archipelagic countries in the world which has a strategic location and has a very large diversity of biological resources. With the potential of marine resources that are owned, they are not immune from the problems they face, such as being a place for illegal fishing practices, especially in sea areas that are directly adjacent to other countries. This study aims to find out how corporate responsibility is as perpetrators of Illegal Fishing in Indonesia and how law enforcement efforts prevent illegal fishing. This study uses normative juridical research methods, namely research that focuses on studying the application of the principles of criminal law in Indonesia regarding the crime of fish theft. The results of the study show that legal protection and prevention of illegal fishing crimes are still not optimal. This can be seen from the lack of public legal awareness of illegal fishing practices and weak law enforcement against illegal fishing crimes. In addition, it is difficult to prove illegal fishing practices carried out by large corporations. Based on this, the authors are of the view that for the sake of realizing legal certainty it is necessary to optimize efforts to prevent and combat illegal fishing practices by involving the community and increasing supervision of illegal fishing practices in Indonesia and the importance of legal unification. provisions on illegal fishing among ASEAN countries. against setting Illegal Fishing practices. The conclusion that can be drawn is that in this case this can be seen from the lack of public legal awareness of illegal fishing practices and the weakness of law enforcement against illegal fishing crimes. In addition, it is difficult to prove illegal fishing practices carried out by large corporations.